Trevor Bryce, 2014 Ancient Syria: A Three Thousand Year History, Oxford: Oxford University Press, ISBN 9780199646678, xix+379pp, £25. - Jamieson, Andrew S. (Buried History: The Journal of the Australian Institute of Archaeology, 2024)
None.